CARRYING CAPACITY ASSESSMENT OF CIBEUREUM WATERFALLTOURISMINGUNUNG GEDE PANGRANGO NATIONAL PARK : Estimation of Gunung Gede Pangrango National Park Carrying Capacity of Cibeureum Waterfall - Anindika Putri Lakspriyanti; Meti Ekayani; Arzyana Sunkar (Department of Forest Resources Conservation and Ecotourism - IPB University, 2020)
Waterfall has long been a popular tourist attraction with increasing number of visitors. High visitation would increase the risk of environmental damage, especially if the location of the tourism object is in a protected area that is still intact and rich in resources. One strategy to reduce the impact of recreational and nature tourism activities is through carrying capacity (CC) analysis. This study aims to 1) analyze the CC visitors of Cibeureum Waterfall and 2) provide a CC-based waterfall tourism management strategy. The research was conducted in October 2018 in Cibeureum Waterfall, TNGGP of West Java. The CC was estimated using the Cifuentes (1992) approach to calculate physical (PCC), real (RCC), and effective (ECC) CCs, by considering various correction factors. Interviews were also conducted with 100 visitors of Cibeureum Waterfall. In addition, interviews were also conducted with 5 key informants from the management side. The results showed that the daily PCC value was 800, exceeding the RCC (173) and ECC (86) values, indicating overcrowding. On the contrary, on weekdays, the number of visitors is below the RCC. These results indicated potential disturbance in Cibeureum Waterfall and its environment during holidays. Carrying capacity-based management alternatives that were recommended include increasing ticket prices on holidays and implement early booking system. From the managerial aspect, it is recommended to involve the NP partners during holidays for in-kind contributions. Keywords: carrying capacity, waterfall tourism, national park